THE INFLUENCE OF PRODUCT QUALITY, PRICE AND PROMOTION ON THE DECISION TO PURCHASE VANS SHOES (Case Study of Students at the Faculty of Economics and Business, Indonesian Christian University) - cantryn, Cathrine Novatisa; Fenny B.N.L. Tobing; Netty Laura S (Fundamental Management Journal, 2024)
The studies aim to understand following aspects of the purchase decision: the presence of a partial influence on the quality of the product on decisions to purchase Vans shoes, existence of a Partial influency on price of decision on purchase of Vans footwear, Presence of an influencing of promotions on purchasing decisions of Vans brand shoe, and the combined impact of products quality, prices, and promotions on Vans’ decisions to buy shoes. Most of populations in these studies were active student at Christian University Indonesia who already wore Vans shoes. Respondents to this study consisted of 58 respondents and sampling techniques use is purposive Sampling. Data analyst techniques use in these studies is Double Linear Regressions use application SPSS 25. Results of these studies show that (1) the quality of the product has partials influence on the purchase decisions of the Vans branded shoes, (2) the price has no partial effects on the buying decision of Vans, (3) the promotion is partially influenced on the purchasing decision for Vans Brand Shoes, and (4) the products quality, prices, and promotions combined have an impact on Vans’ brands shoe purchase decisions. Keywords: Product Qualities, Prices, Promotions, Purchase Decisions